Effect of Fish Oil vs. Resolvin D1, E1, Methyl Esters of Resolvins D1 or D2 on Diabetic Peripheral Neuropathy - Obrosov, Alexander (J Neurol Neurophysiol, 2017)
OBJECTIVE: Fish oil is enriched in omega-3 polyunsaturated fatty acids primarily eicosapentaenoic and docosahexaenoic fatty acids. Metabolites of these two polyunsaturated fatty acids include the E and D series resolvins. Omega-3 polyunsaturated fatty acids and resolvins have been reported to have anti-inflammatory and neuroprotective properties. The objective of this study was to evaluate the efficacy of menhaden oil, a fish oil derived from the menhaden, resolvins D1 and E1 and the methyl esters of resolvins D1 and D2 on diabetic peripheral neuropathy. Hypothesis being examined was that the methyl esters of resolvins D1 and D2 would be move efficacious than resolvins D1 or E1 due to an extended half-life. METHODS: A model of type 2 diabetes in C57BL/6J mice was created through a combination of a high fat diet followed 8 weeks later with treatment of low dosage of streptozotocin. After 8 weeks of untreated hyperglycemia type 2 diabetic mice were treated for 8 weeks with menhaden oil in the diet or daily injections of 1 ng/g body weight resolvins D1, E1 or methyl esters of resolvins D1 or D2. Afterwards, multiple neurological endpoints were examined. RESULTS: Menhaden oil or resolvins did not improve hyperglycemia. Untreated diabetic mice were thermal hypoalgesic, had mechanical allodynia, reduced motor and sensory nerve conduction velocities and decreased innervation of the cornea and skin. These endpoints were significantly improved with menhaden oil or resolvin treatment. However, the methyl esters of resolvins D1 or D2, contrary to our hypothesis, were generally less potent than menhaden oil or resolvins D1 or E1. CONCLUSION: These studies further support omega-3 polyunsaturated fatty acids derived from fish oil via in part due to their metabolites could be an effective treatment for diabetic neuropathy.